IMPORTANCE OF MODERN MANAGEMENT IN BANKS (Journal of Universal Science Research, 2024)
Today, attention is being paid to the banking sector in our country.  Big changes are taking place in the market economy.  This article also describes the importance of modern management, management and other directions in banks.